The Overview Literature Review on Competence-Based Education in The Industrial Engineering Using PRISMA 2020 - Nurcahyanie, Yunia Dwie; Ayu, Manik; Mukhtar, M. Nushron Ali; ., Rusdiyantoro (UNIPA PRESS, 2024)
Structured methods for the methodical re-alignment of professional education programs are needed for the comprehensive integration of the human workforce in digital and sustainable manufacturing and logistics systems. It is believed that investing in engineering education is essential to the advancement of both industry and society. Future engineers, though, will need more than simply a solid foundation in technology. The focus on competence-orientation is often neglected, particularly in the field of Industrial Engineering (IE), and empirically proven success criteria that support the holistic reorientation of engineering education are usually studied. The authors of this work perform a thorough literature review on engineering education, focusing on competence-based engineering education within the field of IE. Additionally, the writers offer beneficial implications for the competence-based for Industrial Engineering students and lectures writings.